Peran Guru Pendidikan Agama Islam Dalam Meningkatkan Kedisiplinan Sholat Berjamaah Siswa - Alimin Alimin; Muhammad Ainur Rofiq (FAKULTAS TARBIYAH UNIVERSITAS QOMARUDDIN GRESIK - JAWA TIMUR, 2023)
This research explores the role of Islamic Religious Education teachers in improving students' discipline in carrying out congregational prayers at MTs Tarbiyatul Islam Karangrejo Ujungpangkah Gresik. The background is based on the phenomenon where some students still depend on teacher instructions to perform prayers; some even hide themselves when asked to do so. Field research methods with a qualitative approach were used to collect data through interviews, observation and documentation. The analysis shows that the teacher's role in fostering student discipline in worship has gone well. Even though there are inhibiting factors that cannot be avoided, the teacher's efforts in providing guidance, direction and explanation have increased students' awareness of carrying out congregational prayers. More than just imposing sanctions for absenteeism from prayer, this approach builds intrinsic awareness in students about the importance of congregational prayer for self-discipline, peace of mind, closeness to God, and strengthening social ties with the surrounding community. These findings illustrate the critical role of teachers in shaping students' spiritual awareness and discipline outside the school environment, creating a more profound impact in forming their character.